The Urgency of Prenuptial Agreements in Building Household Harmony: A Maqashid Syari’ah Perspective - Heni Astuti; Oneng Nurul Bariyah; Usman Alfarisi; Azhar Taufik; Fatma Nurmulia; Dina Febriani; Fakhrurazi; Endang Zakaria (Faculty of Engineering Universitas Muhammadiyah Jakarta, 2024)
This study aims to analyze the values of Maqashid Syari’ah contained in prenuptial agreements and their urgency in fostering harmonious households. The research employs a normative juridical approach through library research, utilizing primary data from statutory regulations such as Law No. 1 of 1974 on Marriage, the Civil Code, the Compilation of Islamic Law (KHI), and related provisions. Secondary data were obtained from literature and academic studies concerning Maqashid Syari’ah and Islamic family law. The results indicate that prenuptial agreements align with the principles of al-kulliyat al-khamsah, namely the protection of religion, intellect, life, lineage, and property. Implementing prenuptial agreements can prevent disputes, safeguard spousal rights, and create families imbued with sakinah, mawaddah, and rahmah. The study recommends wider socialization of prenuptial agreements, emphasizing their role in preserving household welfare rather than merely separating assets.